Effects of vibration training vs. conventional resistance training among community-dwelling older people with sarcopenia: three-arm randomized controlled trial protocol - Lu, Linqian; He, Xiangfeng; Ma, Lin; Liu, Yu; Chen, Nan (Frontiers in Aging Neuroscience, 2022)
Introduction: Sarcopenia is a chronic and progressive disease, which is accompanied by the decline in muscle mass, muscle strength and physical performance with aging, and it can lead to falls, fracture and premature death. The prevention and treatment of sarcopenia mainly includes exercise therapy and nutritional supplement. Exercise therapy is one of the most potential interventions to prevent and/or delay the progression of sarcopenia. Resistance training (RT) as one of the most commonly used exercise types, is widely used in the treatment of sarcopenia, meanwhile vibration training (VT) is a prospective strategy for improving sarcopenia in older people. The aim of our study is to compare the effect of VT and RT in older people with sarcopenia on muscle mass, muscle strength, physical performance, blood biomarkers and quality of life. Methods and analysis: Our study is a 12-week, 3-arm randomized controlled trial with assessor-blinded. The diagnosis criteria for subject recruitment adopts the guidelines for the Asian Working Group for Sarcopenia. 54 subjects who meet the criteria will be randomized into one of the following three groups: VT group, RT group and control group. VT group and RT group will receive a 12-week whole-body vibration training and resistance training program for three times every week, respectively. The primary outcome is lower limb muscle strength and the secondary outcomes including muscle mass, upper limb muscle strength, physical performance, blood biomarkers and quality of life. We will perform assessments for three times at baseline (0 week), after-intervention (12 weeks) and follow-up (24 weeks). The adverse events will also be reported. All outcome measurements will be performed by the same researchers. Data will be saved in the unified database, and the collected data of all subjects will be analyzed by intention-to-treat analysis.